Introduction to the GaLA Conf 2019 Special Issue - Manuel Gentile; Mario Allegra; Heinrich Heinrich Söbke (Serious Games Society, 2019)
This issue contains seven selected articles, which gives an overview of the rich field of serious games. So among the topics covered in this issue there are: • gamification of learning experiences, • serious games in everyday life, • artificial intelligence as a means to significantly increase the effects of serious games, • understanding the effect of learner characteristics on the effects of serious games, • assessing the learning outcomes of serious games systematically, and • games as objects of generative learning approaches.